DAMPAK BULLYING TERHADAP KEHIDUPAN PSIKOLOGIS PESERTA DIDIK - Nurul Fajri; Arif Arif; Hidayani Syam (CV. ADIBA AISHA AMIRA, 2025)
This study examines bullying behaviors and their psychological impact on victims in Muhammadiyah elementary schools. Bullying is defined as intentional or unintentional acts of violence, either verbal or physical, carried out by individuals or groups. The research methodology used is a qualitative case study. Data was collected from teachers, principals, and students who were victims of bullying (primary data) as well as journals and books (secondary data). Data collection techniques included interviews and observations. The results of the study showed that two types of bullying occur, namely physical bullying and verbal bullying. The psychological impacts of bullying on victims include decreased self-confidence, anxiety about the surrounding environment, trauma and reluctance to make friends again, embarrassment, speaking softly, and avoiding eye contact, anger that peaks when bad treatment is continuously received. This study is expected to provide a better understanding of bullying and its impact on the psychological well-being of victims, as well as assist in eflorts to prevent and combat bullying in schools.